Making remittances work : balancing financial integrity and inclusion - Todoroki, Emiko (Directions in development (Washington, D.C.). Finance., 2014)
H.M. Queen Máxima of the Netherlands, United Nations Secretary-General's Special Advocate for Inclusive Finance for Development stated that 'the impact of helping migrants and their families will be lasting and global if we link remittances to other financial services and make them more affordable and more relevant to their needs."" Remittances are a critical source of financing for most developing countries. The importance of remittances goes beyond numbers. For many households in developing countries, they are probably the most stable source of primary or additional income. At the same time,